1994
DOI: 10.1107/s0907444994005287
|View full text |Cite
|
Sign up to set email alerts
|

Refined structure of concanavalin A complexed with methyl α-D-mannopyranoside at 2.0 Å resolution and comparison with the saccharide-free structure

Abstract: The three-dimensional structure of the complex between methyl a-D-mannopyranoside and concanavalin A has been refined at 2.0 A resolution. Diffraction data were recorded from a single crystal (space group P21212~, a = 123.7, b = 128.6, c = 67.2 A) using synchrotron radiation at a wavelength of 1.488 A. The final model has good geometry and an R factor of 19.9% for 58871 reflections (82% complete), within the resolution limits of 8 to 2 A, with F > 1.0tr(F). The asymmetric unit contains four protein subunits ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 23 publications
12
136
2
Order By: Relevance
“…4). As shown in ConA-sugar complexes (Naismith et al 1994), although the main chain positions of the amino acid residues forming the monosaccharidebinding site of ConA remain very similar in both complexed and native structures of ConA, their side chains are altered in the complexed form. Especially, Leu 99 , Tyr 100 and Arg 228 undergo drastic conformational changes upon binding to sugars.…”
Section: Discussionmentioning
confidence: 85%
“…4). As shown in ConA-sugar complexes (Naismith et al 1994), although the main chain positions of the amino acid residues forming the monosaccharidebinding site of ConA remain very similar in both complexed and native structures of ConA, their side chains are altered in the complexed form. Especially, Leu 99 , Tyr 100 and Arg 228 undergo drastic conformational changes upon binding to sugars.…”
Section: Discussionmentioning
confidence: 85%
“…In this way, they can contribute directly to the properties of the protein by influencing its interaction with the sugar. In this context, Naismith et al (10) observed that the waters that are expelled on binding of MeMan in the monosaccharide-binding site of ConA make similar hydrogen bonds with the protein as the sugar oxygen atoms O-4, O-5, and O-6 of MeMan with Asn-14 N-␦2, Leu-99 N, and Tyr-100 N, respectively. A similar observation was made for the water molecules expelled from the surface of the carbohydrate-binding site of Erythrina corallodendron lectin, a galactose/N-acetylgalactosamine-specific legume lectin (38).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of the oligosaccharide, they are replaced by water molecules. The water molecules then compensate for the lack of the polar sugar-protein interaction by sharing the same protein hydrogen-bonding partners as the sugar atoms (10). Not only polar interactions are compensated for.…”
Section: Man(␣1-3)man(␣1-o)me/man(␣1-6)man(␣1-o)me⅐cona Complexes 29193mentioning
confidence: 99%
“…The mannose±conA complex unambiguously identi®ed the binding site and the interactions involved in monosaccharide recognition by the protein. This work has been developed by higher resolution studies of the mannose and glucose complexes (Naismith et al, 1994;Harrop et al, 1996). The lectin itself has now been studied at atomic resolution (Deacon et al, 1997).…”
Section: Introductionmentioning
confidence: 99%